Numerical study of azimuthal sheath structure and asymmetric anomalous erosion in a stationary plasma thruster. (April 2019) - Liu, Hui; Niu, Xiang; Yu, Da-Ren
Abstract : The influence of the azimuthal electron drift on anomalous erosion and the sheath profile in a stationary plasma thruster (SPT) is analysed in this article. It is found that the anomalous erosion has a self-organized structure, which is formed by the interaction between the plasma and the ceramic walls. In order to interpret the mechanism of the azimuthal erosion structure, a particle in cell (PIC) model is developed to simulate the azimuthal sheath. The results show that the electron azimuthal Hall drift due to crossed electric and magnetic field plays a key role in the azimuthal erosion evolution process. Electron Hall drift can generate an asymmetric sheath structure and induce azimuthal sheath oscillation. Furthermore, an asymmetric sheath caused by the integrated effect of the azimuthal irregular wall structure and azimuthal Hall drift will result in the azimuthal movement of ions. Based on the sheath simulated results, an erosion model is used to simulate the azimuthal erosion evolution. An asymmetric erosion profile caused by the azimuthal asymmetric ion sputtering is found.